Oritavancin Versus Daptomycin for Osteomyelitis Treatment After Surgical Debridement - Nicholas W. Van Hise; Russell M. Petrak; Kairav Shah; Melina Diaz; Vishnu Chundi; Mark Redell (Infectious Diseases and Therapy, 2024)
Abstract Introduction Weekly intravenous (IV) oritavancin and daily daptomycin were compared in an outpatient setting following extensive surgical debridement for treating patients with osteomyelitis. Methods This was a retrospective, observational study of patients diagnosed with acute osteomyelitis. Exclusion criteria were the use of Gram-negative antibiotic therapy, use of antibiotics for more than 48 h prior to oritavancin or daptomycin or prior use of > 2 doses of oritavancin or more than 4 weeks of daptomycin. Clinical success was resolution or improvement of symptoms and no further treatment. Data were analyzed with Chi-square test or Fisher’s exact test. Results Consecutive outpatients (n = 150) with acute osteomyelitis who were treated with oritavancin or daptomycin (1:1) following extensive surgical debridement were identified. Staphylococcus aureus was the most common pathogen (n = 117). No patient in either group received prior antibiotic therapy (previous 30 days) or was hospitalized within 90 days prior to surgical debridement. Twenty-one (28%) patients prescribed oritavancin had chronic kidney disease, seven of whom were receiving hemodialysis or peritoneal dialysis. Compared to oritavancin, patients prescribed daptomycin had higher rates of all-cause readmission [odds ratio (OR) 2.89; p < 0.001], more infection-related readmission (OR 3.19; p < 0.001), and greater likelihood of receiving antibiotics post-discontinuation of initial therapy (OR 2.13; p < 0.001). Repeat surgical debridement was required for 68.0% with daptomycin vs. 23.1% with oritavancin (p < 0.001). Conclusions Oritavancin demonstrated a significantly higher rate of clinical success compared to daptomycin, with lower all-cause and infection-related readmissions, reduced need for repeat surgical debridement, and fewer additional antibiotic requirements.